2021
DOI: 10.3389/fpls.2020.602882
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Strategies and Challenges in the Improvement of Blast Disease Resistance in Finger Millet. A Current Review

Abstract: Climate change has significantly altered the biodiversity of crop pests and pathogens, posing a major challenge to sustainable crop production. At the same time, with the increasing global population, there is growing pressure on plant breeders to secure the projected food demand by improving the prevailing yield of major food crops. Finger millet is an important cereal crop in southern Asia and eastern Africa, with excellent nutraceutical properties, long storage period, and a unique ability to grow under ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…africana F 2:3 population has yielded a highly accurate, high‐density genetic map that offers highly significant QTL for critical agronomic traits, especially blast resistance. Magnaporthe oryzae is the most destructive pathogen of finger millet and poses severe threats to subsistence farming as well as development of high‐yielding cultivars (Mbinda & Masaki, 2021; Takan et al., 2004; Takan et al., 2012). Our study shows that wild finger millet accessions could provide blast resistance variation for application in finger millet breeding programs and provides information on several NBS‐LRR genes that have homology to or are orthologs of genes that are known to be responsive to infection by M. oryzae in rice.…”
Section: Discussionmentioning
confidence: 99%
“…africana F 2:3 population has yielded a highly accurate, high‐density genetic map that offers highly significant QTL for critical agronomic traits, especially blast resistance. Magnaporthe oryzae is the most destructive pathogen of finger millet and poses severe threats to subsistence farming as well as development of high‐yielding cultivars (Mbinda & Masaki, 2021; Takan et al., 2004; Takan et al., 2012). Our study shows that wild finger millet accessions could provide blast resistance variation for application in finger millet breeding programs and provides information on several NBS‐LRR genes that have homology to or are orthologs of genes that are known to be responsive to infection by M. oryzae in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing new finger millet varieties with all these important characters is very crucial. Introgression of a healthy and durable resistance to Magnaporathe oryzae in to adapted finger millet germplasm by modern breeding approach has been a goal of many breeding programs [26]. To date, no finger millet variety has been developed @ECRTD-UK: https://www.eajournals.org/ and released yet based on marker assisted selection (MAS) technique.…”
Section: Alternative Breeding Methodologies For Resistancementioning
confidence: 99%
“…This is evident based on the increase in the yearly number of original articles and reviews published after the major epidemics reported in the Cerrado, Brazil, and disease's introduction into both Asia and Africa (Figure 2A). (Rajiv 2017;Sadat and Choi 2017;Cruz and Valent 2017;Mottaleb et al 2018Mottaleb et al , 2019Ceresini et al 2018Ceresini et al , 2019Islam et al , 2020Kamoun et al 2019;Tembo 2019;Yesmin et al 2020;Mbinda and Masaki 2021, Singh et al 2021, Tosa 2021. While some aspects have been given more attention, such as the taxonomy and population genetics (Couch and Kohn 2002;Tanaka et al 2009;Luo and Zhang 2013;Maciel et al 2014;Murata et al 2014;Klaubauf et al 2014;Gladieux et al 2015Gladieux et al , 2018Castroagudín et al 2016;Valent et al 2019), chemical control (Kim et al 2003;Cruz et al 2011Cruz et al , 2019Pagani et al 2014;Rocha et al 2014;Castroagudín et al 2015;Oliveira et al 2015;Dorigan et al 2019;D'Ávila et al 2021;Ascari et al 2021) and host genetic resistance (Cruz et al 2016b;Anh et al 2018;Rocha et al 2019;…”
Section: Economical and Scientific Importancementioning
confidence: 99%
“…The integration of several tactics from cultural, genetic and chemical control methods is currently the best strategy for managing wheat blast (Ceresini et al 2018(Ceresini et al , 2019Mbinda and Masaki 2021). Climate is known to be a major driver of the occurrence and intensity of wheat blast outbreaks.…”
Section: Wheat Blast Managementmentioning
confidence: 99%